Modeling and simulation of intermittent drying of high moisture foods - Filippin, A. P. [UNESP]; Tada, E. F. R. [UNESP]; Thomeo, J. C. [UNESP]; Mauro, M. A. [UNESP]; Carcel, J. A.; Clemente, G.; GarciaPerez, J. V.; Mulet, A.; Rossello, C. (Univ Politecnica Valencia, 2018)
This study aimed at the modeling and simulation of intermittent drying to be applied to highly deformable moist foods such as apples. Mass transport modeling considered two stages: the first at 95, 85 and 75 degrees C air temperatures, and the second at 60 degrees C. The shrinkage was correlated with the sample moisture and included in the model that was solved by the finite differences method. The first stage temperatures affected the water diffusivity in the second stage. This model was suitable for simulating the water profiles during the two-stage intermittent drying, showing an efficient fitting to the experimental data.
Keywords: thermal intermittence; coefficient diffusion effective; shrinkage; apple drying